Partial purification and biological characterization of active components from pseudomonas aeruginosa culture filtrate causing corneal opacification in vitro geneses and muscle glycolysis - Buenaflor, Gertrudes G. (Theses--(MS in Biochemistry) University of the Philippines Manila)
The search of the corneal opacifying components found in the crude extracellular protein concentrate of Pseudomonas aeruginosa was done. The active principles were partially purified by filtration, ammonium sulfate precipitation, dialysis, diethylaminoethyl ion exchange chromotography and gel filtration. The in vitro cornea opacifying principles were found to be heat sensitive, non-dialyzable, and ammonium sulfate precipitable. Fractionation studies showed that these activities consisted of a low- and a high-molecular weight components which were anionic and do not possess protease activity. Preliminary in vivo test of an active fraction obtained from sequential chromatography was conductedThe search of the corneal opacifying components found in the crude extracellular protein concentrate of Pseudomonas aeruginosa was done. The active principles were partially purified by filtration, ammonium sulfate precipitation, dialysis, diethylaminoethyl ion exchange chromotography and gel filtration. The in vitro cornea opacifying principles were found to be heat sensitive, non-dialyzable, and ammonium sulfate precipitable. Fractionation studies showed that these activities consisted of a low- and a high-molecular weight components which were anionic and do not possess protease activity. Preliminary in vivo test of an active fraction obtained from sequential chromatography was conducted
Keywords: Cornea; Corneal Opacity